The Effect of Gamma-Irradiated Nitrate-Reducing Bacteria in Decreasing the In Vitro Production of Methane by Buffalo Rumen Liquid - R. Rahmani; M.R. Pikoli; I. Sugoro (Atom Indonesia, 2019)
Ruminant livestock undeniably contributes to the increase of greenhouse gases by emitting methane. One strategy used to reduce methane emission is by applying nitrate-reducing bacteria (NRB). Utilizing active NRB has a side effect of acidosis in rumen liquid in an uncontrolled condition. Alternatively, NRB can be applied in an inactive form. The aim of this study was to examine the use of gamma irradiation on NRB to be used for decreasing methane production by buffalo rumen liquid. The examination was performed in vitro and involved comparison to other treatments, which were active NRB, autoclaved NRB, and without NRB. The result showed that the NRB in either active or the inactive conditionaffected fermentation of the rumen microorganisms. There were differences in pH values, digestibility of organic matters, ammonia, total and partial volatile fatty acids, and methane production between all treatments after 24 and 48 h of incubation. All treatments showed significant differences for each parameter, except for the gas production (p ≤ 0.05). The irradiated NRB produced slightly more methane, i.e. 3.0 and 10.4 ml/200 mg after 24 and 48 h incubation, respectively, compared to the active NRB, autoclaved NRB, and no-NRB-addition treatments, i.e., 2.0 and 8.0; 7.8 and 11.7; 8.0 and 12.4 ml/200 mg, respectively. In conclusion, the irradiated NRB has a potency as a supplement feed for buffaloes to reduce methane production without the risk of acidosis in the rumen liquid.